2022
DOI: 10.21203/rs.3.rs-2191906/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A better alignment between chronotype and school timing is associated with lower grade retention in adolescents

Abstract: Schools start early in the morning all over the world, contrasting with adolescents’ late chronotype. These early school timings have negative consequences on academic performance (i.e. grades), which are worse for students with later chronotypes. This academic disadvantage has been associated with the misalignment between school schedule and adolescents’ internal timing, but it is unclear how this affects students’ academic success beyond their grades. To address this gap in knowledge, we studied how school t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 64 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…The academic advantage the early chronotype students had in the morning over those with later chronotypes was substantially diminished, and even reversed, when school started late in the day. An additional analysis of this sample revealed that the impact of synchrony is greater for math-related subjects than for language subjects (Ferrante et al, 2022).…”
Section: Academic Performancementioning
confidence: 89%
See 1 more Smart Citation
“…The academic advantage the early chronotype students had in the morning over those with later chronotypes was substantially diminished, and even reversed, when school started late in the day. An additional analysis of this sample revealed that the impact of synchrony is greater for math-related subjects than for language subjects (Ferrante et al, 2022).…”
Section: Academic Performancementioning
confidence: 89%
“…Studies on delayed start times (often in the range of 30-60 min) report increases in sleep time, improvements in mood and attentiveness, and reductions in tardiness and absenteeism, disciplinary problems, and car accidents (Gomes de Araújo et al, 2022;Kelley et al, 2015Kelley et al, , 2017Thacher & Onyper, 2016;Wheaton et al, 2016). Despite these important behavioral improvements and the increase in total sleep time, reports of academic-achievement gains are relatively rare, with several studies reporting small or even no benefits from additional sleep (e.g., Alfonsi et al, 2020;Boergers et al, 2014;Dunster et al, 2018;Hinrichs, 2011;Owens et al, 2010;Ferrante et al, 2022;Thacher & Onyper, 2016;Wheaton et al, 2016). We note that early school start times, even when delayed by an hour, create a mismatch with adolescents' optimal times.…”
Section: Academic Performancementioning
confidence: 99%
“…Most published studies endorse the implementation of later SSTs by reporting a wide variety of benefits: longer sleep duration (Carvalho‐Mendes et al, 2020; Dunster et al, 2018; Goldin et al, 2020; Meltzer et al, 2021; Rodríguez Ferrante et al, 2022; Thacher & Onyper, 2016), lower levels of SJL (Carvalho‐Mendes et al, 2020; Goldin et al, 2020; Widome et al, 2020), improvement of students' well‐being (Arrona‐Palacios et al, 2021; Boergers et al, 2014; Lo et al, 2018), lower rate of car incidents (Danner & Phillips, 2008; Vorona Robert Daniel et al, 2011), among others (Dunster et al, 2018; Rodríguez Ferrante et al, 2022b). Globally, current evidence clearly shows that later SSTs are associated with benefits for adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility to reduce the negative outcomes associated with early SST during adolescence is to delay SSTs. Later SSTs had been associated with better outcomes in adolescents, including longer sleep duration, lower SJL, better academic performance and lower rate of vehicular accidents, among other benefits (Daniel et al, 2011; Dunster et al, 2018; Goldin et al, 2020; Rodríguez Ferrante et al, 2022a, 2022b; Wahlstrom, 2002). However, these improvements were not always observed (Das‐Friebel et al, 2020; Hinrichs, 2011), and previous meta‐analyses showed significant variability in the effect size of delayed SSTs on different outcomes (Bowers & Moyer, 2017; Yip et al, 2022), suggesting that some factors might be acting as moderators of the overall effect.…”
Section: Introductionmentioning
confidence: 99%